2021
DOI: 10.3390/brainsci11080963
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Bases of Egocentric Spatial Representation for Extracorporeal and Corporeal Tasks: An fMRI Study

Abstract: (1) Background: Humans use reference frames to elaborate the spatial representations needed for all space-oriented behaviors such as postural control, walking, or grasping. We investigated the neural bases of two egocentric tasks: the extracorporeal subjective straight-ahead task (SSA) and the corporeal subjective longitudinal body plane task (SLB) in healthy participants using functional magnetic resonance imaging (fMRI). This work was an ancillary part of a study involving stroke patients. (2) Methods: Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Among the various pattern of brain activations, the work reported that a specific brain structure (i.e., the left Superior Parietal Lobule SPL) was significantly more activated in first-, than in third-, person perspective. Interestingly, other studies investigating the neural correlates of representing the environment from egocentric perspectives in a broader sense reported the same selective activation 53 55 . Such set of evidence seems to be in line with the known role of the SPL in representing nearby stimuli in body-centered coordinates 56 .…”
Section: Discussionmentioning
confidence: 65%
“…Among the various pattern of brain activations, the work reported that a specific brain structure (i.e., the left Superior Parietal Lobule SPL) was significantly more activated in first-, than in third-, person perspective. Interestingly, other studies investigating the neural correlates of representing the environment from egocentric perspectives in a broader sense reported the same selective activation 53 55 . Such set of evidence seems to be in line with the known role of the SPL in representing nearby stimuli in body-centered coordinates 56 .…”
Section: Discussionmentioning
confidence: 65%
“…The MOG, as part of the lateral occipital complex, is a higher-order visual cortical region that processes spatial information about a viewed object, such as shape (Cant et al, 2009), location (Liu et al, 2017; Galati et al, 2001; Saj et al, 2014; Chen et al, 2012; Reiner et al, 2010), and orientation (Leplaideur et al, 2021; Saj et al, 2019). A recent meta-analysis (Derbie et al, 2021) showed that the rMOG is activated when a task requires visuospatial processing of information about an object in reference to the participants’ own body (egocentric spatial coding), rather than to other objects (allocentric spatial coding).…”
Section: Discussionmentioning
confidence: 99%
“…Stephanie Leplaideur et al [3] explored the neural bases of egocentric spatial representation in healthy participants using fMRI. Comparing two tasks testing the extracorporeal and corporeal spatial representation of body in space, they revealed the presence of parieto-occipital networks, with a right-hemispheric dominance, associated with both extracorporeal and corporeal tasks.…”
mentioning
confidence: 99%